The Effect of Lavender Aromatherapy on Menstrual Pain Intensity (Dysmenorrhea) on the Nursing Students - Raufuddin, Raufuddin; Kaonang , Mahardika Putri; Yobel, Sosilo (Universitas Airlangga, 2022)
Introduction: Most women often experience menstrual period complaints such as menstrual pain or dysmenorrhea. One of the non-pharmacological ways to lower the pain level in a person experiencing dysmenorrhea or menstrual pain is lavender aromatherapy. Aromatherapy lavender is a method that uses lavender essential oil containing linalool and linalyl acetate which is beneficial in reducing painful menstruation. The purpose of this research is to know the difference in dysmenorrhea intensity before and after giving lavender aromatherapy to a nursing student at a higher nursing education in Surabaya, Indonesia. Method: This study used a pre-pre-experimental design with one group pre-test and post-test design method. The research was done on 103 nursing students who have undergone dysmenorrhea using a quota sampling technique. Analysis of the data used the Wilcoxon Signed Rank Test with α- levels significance = 0.05 (p=0.05). Results: The results showed a difference in menstrual pain (dysmenorrhea) before and after giving lavender aromatherapy. p-value was <0.001 which means there is a difference in menstrual pain intensity (dysmenorrhea) before and after giving lavender aromatherapy to a nursing student at a higher nursing education in Surabaya, Indonesia. Conclusions: Lavender aromatherapy is reducing menstrual pain intensity in the nursing student at STIKES Artha Bodhi Iswara Surabaya. Lavender aromatherapy is one of the non-pharmacological methods that can reduce the pain intensity of dysmenorrhea in women.